Les prés vergers de pommiers à cidre et les agroforêts de cacaoyers - Samuel Perichon (Projets de Paysage)
The new edition of the article “A Non-nostalgic Goodbye to Brittany’s standard Orchards”, published in the conference report of the École nationale supérieure du paysage de Versailles (2001), gives the opportunity to offer some comparative elements with other fruit-growing regions in which we also conducted some surveys on several generations of farmers of the same family. A tropical culture – cocoa growing – seems to illustrate particularly well the recent evolution of agriculture worldwide, and the diverging opinions it raises through the generations. Our comparative analysis is based on the results of the researches we led in the regions of Guayas (Ecuador) and of Chiapas (Mexico). The various testimonies bring light to the different reactions – whose origins can be found less in a characterized geographical context than in an unequal appropriation of the technical and agronomical innovations, developed by the research institutes or by some multinational firms. The public policies have a great influence on the strategies of exploitation favoured by the farmers, in the sense where they offer them – deservedly or not – some economic perspectives. The food industry, in its largest meaning, also destabilize the rural identity by discrediting the local know-how – including the rural practises and the cultural varieties. In the three regions mentioned, each one of them corresponds to fruit lands recognized on a national and/or international scale with a quite close final assessment.